Les rituels : des espaces de marge pour construire sa place - Françoise Hatchuel (Recherches en Éducation)
The present article shows how ritual practices can be considered as secured spaces where individuals can experiment new possibilities. A synthesis of different rituals is first presented, demonstrating how they commonly allow one to connect oneself (to other people in the case of rites of interaction, to another version of oneself in the case of rites of passage, or to another supernatural world in the case of religious rites). They also commonly encompass a performative dimension. After identifying a number of studies on school rituals, the author focuses on the rites of interaction in the learning process. The margin in which everyone can experience the ritual for him- or herself, as well as appropriate it for him- or herself, is what distinguishes a ritual from a procedure. In this case, procedures do not guide the action, they define it. The author also focuses on the rites of passage, through which one experiences a personal process within a collective frame, and will irreversibly occupy a new social place. This requires a certain part of the psychic world to remain socially invisible. Following an analysis of obstacles, particularly regarding the psychic and the school’s role, the article concludes with the notion of “anthropologization” to define the process that allows one to feel authorized to live as a member of the community of human beings.